Pengaruh Penerapan Sistem Administrasi Perpajakan Modern terhadap Kepatuhan Wajib Pajak (Survey Terhadap Kantor Pelayanan Pajak Pratama Bandung Bojonagara) - Sinta Setiana; Tan Kwang En; Lidya Agustina (Universitas Kristen Maranatha, 2010)
Efforts through programs and activities of tax administration reform are realized through the implementation of modern tax administration system is intended to encourage taxpayer compliance. Basically, the administration of the tax system which includes service tax and tax law enforcement affect taxpayer compliance.Therefore, the increase in community service became one of the important points of the overall tax administration reform in the DJP.The purpose of this research is to know how to influence the implementation of modern tax administration system of taxpayer compliance in Bojonagara KPP Pratama Bandung. The research data is processed using multiple regression analysis. Based on the results of this study concluded that the application of modern tax administration system on the influence of KPP Pratama Bandung Bojonagara on taxpayer compliance at a significance level á = 0.10. This is indicated by a large impact from the application of modern administrative system is only 17.2% while the remaining 82.8% is influenced by factors other than the variables studied. Results of hypothesis testing showed that the application of modern administrative system is partly within the organizational structure, organizational procedures, organizational strategy, and organizational cultures affect taxpayer compliance. Keywords: Modern Tax Administration System, Organizational Structure,Organization Procedures, Organizational Strategy, Organizational Culture, Taxpayer Compliance